Meter means measure: the story of the metric system - Hirsch S Carl (New York : Viking Press, 1973)
Discusses the creation and development of the metric system and explains why its adoption by the United States is both inevitable and desirable.
Bibliography: p. [121]
Keywords: Metric system -- Juvenile literature; Metric system; Measurement